A preliminary Study on the Improvement of the Ecological Corridor in Paddy Fields†. (26th November 2014) - Chen, Rong‐Song; Wang, Kuo‐Liang; Wu, Chia‐Ying
Abstract The ecological engineering of rivers has been emphasized in recent years; however, scant attention has been focused on the ecological environments of paddy fields and irrigation canals. In this study, a paddy field in Yuanli Township, Miaoli County, Taiwan, was used as a test field. We improved the ecological corridor, ensuring the continuity of the irrigation canal and paddy field, thereby enabling a constant flow of water in the longitudinal section of the paddy field corridor to facilitate smooth upstream migration of fish. Fish could also migrate upstream in the lateral section of the paddy field. Subsequently, loach were used to assess the effect of an enhanced rock pile in a pool area of the simplified paddy fishway, and fish were allowed to migrate up and down the paddy field and irrigation canal. The results indicated that the difference in water levels (i.e. a bottleneck for creating an ecological corridor) was enhanced by the simplified paddy‐field fishway and enhanced rock pile. In addition, removing bottlenecks along the ecological corridor enabled fish and shrimp to migrate in the longitudinal and lateral directions. Copyright © 2014 John Wiley & Sons, Ltd.